Tunisia : Third Review under the Extended Fund Facility, and Request for Waiver of Applicability and Modification of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2018)
The government has strengthened policy and reform implementation in recent months. All Quantitative Performance Criteria (QPCs) for end-March and three out of nine Structural Benchmarks (SBs) for the Third Review were met. One additional SB was implemented with delay. Growth picked up to 2.5 percent in the first quarter, and confidence has improved, albeit it continues to be affected by divisions in the coalition government, risks of security and migration spillovers from Libya, and higher international oil prices. Inflation has accelerated and weighs on the purchasing power notably of the less well-off, while international reserves remain below prudent levels.